(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The purpose of the study was to compare theanthropometric characteristics and somatotype of the Allahabad University’smale basketball players and Foot Ball players. Sixty three sportspersons (FootBall=36 and basketball=27) of age group 18-25 years were selected fromdifferent colleges affiliated to Allahabad University, U.P., India. All theparticipants were assessed for height, weight, breadths, girths and skin foldthickness. An independent samples t-test revealed that basketball players hadsignificantly higher height (p